Construction and structure-activity mechanism of polysaccharide nano-selenium carrier. (15th May 2020) - Hu, Shuqian; Hu, Weicheng; Li, Yanru; Li, Shujing; Tian, Huafeng; Lu, Ang; Wang, Jianguo
Graphical abstract: Highlights: The water solubility of polysaccharides was improved by sulfation modification. The water-soluble sulfated polysaccharides were used as stabilizer. Size-controlled and stable nano-selenium particles were prepared via one-step way. Size-dependent bioactivities of the prepared nano-selenium were evaluated. Abstract: In this study, a series water soluble sulfate polysaccharides (SPS) with different degrees of substitutions (DS = 0.02∼0.28) were prepared using a linear water-insoluble β -d -(1→3)-glucan. SPS-1, SPS-3 and SPS-7 with substitution degrees of 0.02, 0.06 and 0.25 were used as templates to prepare stable and size controlled selenium nanoparticles (SeNPs) with diameter from 54.35 to 123.04 nm using one-step method. The selenium contents of SPS-SeNPs with large, medium and small sizes were 0.172 %, 0.274 % and 0.305 %, respectively. SPS-SeNPs was confirmed to inhibit the production of nitric oxide (NO) in RAW 264.7 inflammatory macrophages induced by lipopolysaccharide (LPS), and downregulated the mRNA expression of TNF- α, IL-1 β and iNOS. The results indicated that SPS-SeNPs had significant anti-inflammatory activity. Moreover, SPS-SeNPs with smaller size showed higher anti-inflammatory effects. All of these results suggest that SeNPs-SPS carriers have anti-inflammatory in concentration-dependent and size-dependent model.